Case Study Learning Model to Improve 6C Competencies through Short Story Text Learning in Middle Schools - Mukhyidin; Gloriani, Yusida; Mascita, Dede Endang (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to examine and develop a case study learning model to improve 6C competency by implementing a case-based learning ( CBL ) model. The problem formulated in this research includes: how is the development, implementation and feasibility of a case-based learning model to improve students' soft skills in learning to write short stories? By applying an R&D research design and the ADDIE approach, this research took data sources from teachers and junior high school/MTs students. in District. Change District. Indramayu. The results of this research show that based on the results of the needs analysis, it is necessary to develop a learning design that is able to grow and improve the potential of students' soft skills , namely a case study learning design. The development process is carried out by formulating Learning Outcomes (CP), Learning Objective Flow (ATP), and teaching modules. The implementation of this learning design was carried out in two trial stages, namely on a small scope and a wider scope. The implementation syntax of this case study learning model is simplified to suit the abilities of junior high school students. Overall, this learning design is declared suitable for use in the field. The results of the trial application of this learning design show that the average ability of students in carrying out the learning process of writing short stories by applying case study-based learning and the average soft skills competency achieved by students after participating in learning by applying case-based learning design is included in the category "Good".